Intracranial meningioma. - Sheporaitis, L A; Osborn, A G; Smirniotopoulos, J G; Clunie, D A; Howieson, J; D'Agostino, A N (American Journal of Neuroradiology, 1992)
This case shows many of the imaging features classically associated with meningiomas. The illustrations show common location, shape, and local effects as well as enhancement characteristics. Hyperostosis and bone destruction, a fluid "cleft" surrounding the extraaxial mass, gray-white interface displacement, and secondary intraparenchymal changes are correlated with gross pathology findings. These key features are summarized in Table 1 and the composite anatomic diagram (Fig. 6).